Psychosocial Quality of Life and Its’ Correlates in People Serving Prison Sentences in Penitentiary Institutions - Talik, Elżbieta (International journal of offender therapy and comparative criminology, 2021)
The aim of the present study was to identify and analyze the determinants of prison inmates’ psychosocial quality of life (PQol) as a positive and negative correlates. Three hundred ninety prison inmates were recruited from the correctional facilities administered by the Warsaw District Inspectorate of Prisons. Data were collected by means of the SQLQ, SOC-29, SWS, SPI/TPI, SIPR, COPE, GSES questionnaires and analyzed by means of SEM. The positive correlates for prison inmates’ PQol are: sense of coherence, self-efficacy, intensity of religious attitude, social support, and trait curiosity. Among the strategies of coping with stress, only seeking social support for emotional reasons is a significant factor that directly predicts PQol. Substance use and planning play only a mediating role in PQol prediction. The negative correlate for inmates’ PQol is trait depression. Contrary to predictions, anxiety is not a negative correlate—as noted above, it is associated with a positive score on PQol.